La politique de restauration des peintures des musées nationaux (1930-1950) - Fernando Suárez San Pablo (Les Cahiers de l'École du Louvre)
After painting conservators were recruited by the Musées Nationaux in 1935, a vast campaign of restoration of paintings, for the most part belonging to the Musée du Louvre, took place. More than 600 paintings were restored between 1936 and 1950 in the new workshop set up in the Louvre where the restorers Lucien Aubert, Pierre Michel, Pierre Paulet, René Longa, Edgard Aillet and Georges Zezzos worked under the supervision of Jean-Gabriel Goulinat.The present article aims to analyze the activity developed during this period exploring its origins at the end of the 1920s. The needs of the Musées Nationaux in terms of the organisation and practice of restoration, which this workshop met, are thus illustrated by the initiatives implemented by an administration that devoted itself to the reinforcement of the modes of supervision of the restorers it hired.